Pengembangan Soal Model AKM Numerasi Pada Domain Konten Geometri dan Pengukuran Untuk Siswa Kelas VIII SMP - Berliana, Audrey Putri; Masriyah, Masriyah (MATHEdunesa, 2024)
World Economic Forum in 2015 emphasized that there are six basic literacy which are 21st century skills that must be mastered, one of which is numeracy. However, students experience difficulties in solving AKM numeracy questions on geometry material because these questions require reasoning abilities. This research using the Tessmer (1993) development model aims to describe the process and results of developing numerical AKM model questions in the geometry and measurement content domains for class VIII students of junior high school that are valid, practical, effective, and reliable. The research instruments used included question sheets, question validation questionnaires, teacher response questionnaires, and student response questionnaires. The results of the study showed that the questions on the AKM numeration model included good quality questions. The numerical AKM model questions meet the valid criteria as indicated by the mode of assessment by the expert which is 3 (good validity criteria) and based on analysis of the validity of the questions (in the category of medium and high validity) and the reliability of the items (in the category of high reliability); fulfilling practical criteria is shown by achieving a good assessment category from the teacher's response questionnaire; fulfilling the effective criteria is shown by achieving a good or very good assessment category from the students' responses and students can express the numeracy abilities of the seven numeracy abilities in working on the questions.